Courageous Methods in Cultural Psychology - Watzlawik, Meike; Salden, Ska. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Innovative research requires courageous methods. With this in mind, Courageous Methods in Cultural Psychology invites students and post-graduate researchers to develop methods that will let them grasp phenomena of interest more fully. Readers will learn how to use established methods, and may be asked to develop them further by combining single steps of extant procedures, or by taking a completely new approach to data collection and analysis. In this book, diverse researchers present projects in which they have tried to do just that. A comprehensive process - from narrowing down research questions to collecting and analyzing data - is given in detail, followed by critical reflections on how well the authors have understood and shared complex realities. Project presentations are framed by theoretical chapters that deal with the challenges and opportunities of cultural psychology and interdisciplinary research. Courageous Methods in Cultural Psychology is sure to inspire and encourage those who wish to venture on new roads "into the wild." Courageous Methods in Cultural Psychology introduces research projects from various subdisciplines of the social and human sciences, each of which was conducted with a cultural-psychological reference in mind. The book strives to emphasize diversity and the added value of interdisciplinary exchange, something that is often neglected in research and needs to be encouraged. Through detailed descriptions of the research process, this book will support and guide readers on how to approach a research question when concrete ideas about the appropriate method may be lacking. Each chapter shows how methods are adapted to the phenomenon of interest, inviting the reader to proceed in a similar way. Within psychology, most methods are very language-based, which means that researchers analyze questionnaires, diaries, transcripts of interviews, and the like. Materials such as these play a major role in this book, but we have also tried to include other data sources. For example, art and architecture are also brought into the book's purview, to help researchers and students rethink the construction of knowledge and data as such.
Chapter 1. The Crooked Relationship Between Method and Matter -- Chapter 2. Reading Traces in Eels and Faces: Historical Roots of Semiotic Thinking in Psychology -- Chapter 3. Why We Have Two Ears: Particularized Meaning Beyond Language, or The Benefits of Musicalization in Research -- Chapter 4. Unfrozen: A Voice-Centered Listening Analysis of Self-Acceptance -- Chapter 5. Breaking Down Complex Realities: The Exploration of Children's Prosocial Actions Using Photographs -- Chapter 6. How Do People Make Meaning? A Methodological Dialogue between Social Anthropology and Developmental Psychology -- Chapter 7. Studying the stream of experience at memorial sites: The subjective camera methodology -- Chapter 8. Multimodal Interaction Analysis in Cultural Psychology research -- Chapter 9. Multisensory Ethnography as a Tool for Reconstructing Spatial Identities -- Chapter 10. "I had to google it": Toward an embodied pedagogy in psychology -- Chapter 11. Art as a Domain of Psychological Reality - Morphological Art Research and Art Coaching -- Chapter 12. Collaborative Realities.
Keywords: Psychology; Psychology-Methodology.; Social psychology; Ethnopsychology; Linguistics; Sociology; Behavioral Sciences and Psychology; Psychological Methods; Cultural Psychology; Psychological Anthropology; Linguistics; Sociology